Structural and Seismic Behavior of Square-Framed Tube Buildings With Peripheral T-Shaped Walls in Moderate Seismic Zones - Debashis Mallick; Mohammad Al Amin Siddique (Advances in Civil Engineering)
Due to the demand for massive urbanization, more high-rise buildings need to be constructed in major cities. The framed tube structural system can be an effective framing technique for this case. This system comprises tightly spaced peripheral columns connected by deep spandrel beams. Reinforced concrete structural walls provide substantial lateral strength and stiffness to limit damage when structures are subjected to ground shaking. In this paper, T-shaped shear walls replace the peripheral columns to obtain better performance. The reduced cost of columns, walls, and beams of square-shaped framed tube structures with peripheral T-shaped walls compared to the column is in the range of 8%–18%. The shear lag factor for the ground floor of square-shaped framed tube structures is also reduced from 4% to 56% for different structural configurations. The concrete quantity of columns, walls, and beams of square-shaped framed tube structures with peripheral T-walls is reduced by 6%–19%. The longitudinal reinforcement quantity of columns, walls, and beams is also reduced by 12%–25%. The reaction force for the foundation design of square-shaped framed tube structures with peripheral T-shaped walls lies between 2% and 11% less than the square-shaped framed tube structures with peripheral columns. The seismic performance level of buildings with peripheral T-walls is immediate occupancy (IO) for the hazard level corresponding to service level earthquake (SLE), design basis earthquake (DBE), and maximum considered earthquake (MCE), while IO to life safety (LS) for the buildings having peripheral columns. The plastic hinge formation of considered buildings with peripheral columns is 1%–5%, 2%–7%, and 7%–12%, SLE, DBE, and MCE, respectively, while the buildings with peripheral T-walls are insignificant. The drift ratio of buildings with peripheral walls is less than that of those with peripheral columns.